2015
DOI: 10.1515/nor-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Theory in Financial Crisis Journalism?

Abstract: The present article analyses press coverage of the dramatic finance crisis and the ensuing European debt crisis in Europe, in three decisive periods. The authors conduct quantitative and qualitative content analyses of two major mainstream Norwegian newspapers, Aftenposten and Dagbladet, employing concepts and methods from framing theory, to analyse coverage in the framework of two contesting schools in economics.The study finds traces of discussions of finance brokers' ethics and some discussions of governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…For example, the literature review demonstrated how similar neoliberal values were used to report on the financial crisis across Europe (Bjerke and Fonn, 2015;Doudaki et al, 2016;Preston and Silke, 2011) and as such, our study contributes to this wider project of investigating media reporting of the financial crisis using situated case studies. Taken together, these studies suggest that neoliberalism has become the underlying value of media reporting, informing the construction of public discussion.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…For example, the literature review demonstrated how similar neoliberal values were used to report on the financial crisis across Europe (Bjerke and Fonn, 2015;Doudaki et al, 2016;Preston and Silke, 2011) and as such, our study contributes to this wider project of investigating media reporting of the financial crisis using situated case studies. Taken together, these studies suggest that neoliberalism has become the underlying value of media reporting, informing the construction of public discussion.…”
Section: Discussionmentioning
confidence: 69%
“…Studies point to the predominantly neoliberal analysis of the financial crisis both in the UK and across Europe (Berry, 2016a;Bjerke and Fonn, 2015). This paper extends this analysis by exploring the difficulties of presenting alternative models to capitalism in the media, illustrating the point by a discursive frames analysis of reporting on the Cooperative Bank.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Essa tendência pode ser observada, por exemplo, em vários estudos realizados sobre o colapso do sistema financeiro americano e a cobertura dos media europeus sobre a crise económica da Zona Euro. As dificuldades em empreender um jornalismo investigativo quando as redações cortam funcionários e o poder manipulador das relações públicas financeiras estão entre os principais fatores identificados pelas pesquisas para explicar porque é que o jornalismo económico falhou em reconhecer as evidências que davam conta da crescente possibilidade de colapso do sistema financeiro ocidental e porque é que a agenda dos media na crise da Zona Euro foi orientada para as elites políticas e económicas e para o consenso (Lloyd & Marconi, 2014;Bjerke & Fonn, 2015;Picard, 2015).…”
Section: Os Media Sob a Ordem Neoliberalunclassified